2015
DOI: 10.1016/j.ejvs.2014.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of Available Patient Reported Outcome Measures for Intermittent Claudication: A Systematic Review Using the COSMIN Checklist

Abstract: The quality of the validation of most disease specific PROMs for IC is alarming, hampering all conclusion based on these PROMs. Considering the results, the PAD quality of life questionnaire (PADQOL), Intermittent claudication questionnaire (ICQ) and the Vascular quality of life questionnaire (VascuQol) might be appropriate PROMs for health related quality of life, while the Walking impairment questionnaire (WIQ) and Estimate ambulation capacity by history questionnaire (EACH-Q) appear suitable PROMs for funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 52 publications
1
55
0
2
Order By: Relevance
“…Subsequently, most of the studies were rated low in terms of quality. Another systematic review of PROMs in patients with IC found that the methodological quality of most studies ranged from poor to fair [35]. Our review supports the findings of the review by Conijn et al [35] confirming the need for better quality studies of PROMs.…”
Section: Discussionsupporting
confidence: 87%
“…Subsequently, most of the studies were rated low in terms of quality. Another systematic review of PROMs in patients with IC found that the methodological quality of most studies ranged from poor to fair [35]. Our review supports the findings of the review by Conijn et al [35] confirming the need for better quality studies of PROMs.…”
Section: Discussionsupporting
confidence: 87%
“…This is a well validated measure using 5 sub-scales: Social Relationships, Self-Concepts and Feelings, Symptoms and Limitations in Physical Functioning, Fear and Uncertainty, and Positive Adaptation. 31 …”
Section: Methodsmentioning
confidence: 99%
“…Improvement of 11.5 points and 13.7 points on the PADQOL-symptom and limitation in physical functioning (factor 3) and ICQ scales respectively, appear 2.2 and 4.7 times greater than when these patients were part of the WALK only group of the original study [17]. These data should remove doubts about the fidelity of FES contribution to improving quality of life measures for patients with PAD and IC [20,23]. In the original study we reported that the 4 other factors of the PADQOL questionnaire (Social Relationships, Self-Concepts and Feelings, Fear and Uncertainty, and Positive Adaptation) did not change significantly over time in either the FES+Walk or Walk groups.…”
Section: Discussionmentioning
confidence: 86%
“…In the original study we reported that the 4 other factors of the PADQOL questionnaire (Social Relationships, Self-Concepts and Feelings, Fear and Uncertainty, and Positive Adaptation) did not change significantly over time in either the FES+Walk or Walk groups. It is conceivable that these factors of the PAD quality of life questionnaire might be appropriate health-related quality of life measures, but do not reflect or interrelate to walking impairment or functional status of PAD patients who are able to ambulate in the home environment [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation